The Influence of the Saints and Blessed of the Catholic Church on the Cultural Heritage of Kraków - Izabela Sołjan; Bożena Gierek (Religions)
Kraków is a unique city on the map of Europe. As early as 1978, it was included in the UNESCO World Heritage List as one of the first 12 sites in the world. It has been a member of the Organization of World Heritage Cities since 1995. The city’s cultural heritage also consists of its religious heritage, including the heritage associated with people who lived in Kraków over the centuries and whom the Catholic Church has recognized as saints or blessed. So far, 23 people closely associated with Kraków have been declared blessed or saints by the Church. Their cult has resulted in the establishment of more than 20 worship centres in Kraków, with two international sanctuaries among them. The legacy of the saints is also the ideas and values they professed, which became evident in the activities they performed. The aim of this article is to present the cultural heritage of these saints, with particular emphasis on their intangible dimension, especially related to the social activity of the saints in the city. This article is based on an analysis of numerous materials devoted to the saints and the cult centres associated with them.